Political mergers as coalition formation: An analysis of the Heisei municipal amalgamations - Eric Weese (Yale University, Economic Growth Center, 2013)
Due to moral hazard problems, municipal mergers in Japan did not result in as many amalgamations as a central planner would have chosen. The inefficiency of the decentralized mergers is calculated using structural parameter estimates based on observed mergers and actual national government policies. Estimation requires neither an equilibrium selection assumption nor the enumeration of all possible mergers.
Keywords: C63; D71; H77; 330; Boundaries; Mergers; Moment Inequalities; Municipalities